1995
DOI: 10.1111/j.1365-2796.1995.tb01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Daytime sleepiness, snoring and gastro‐oesophageal reflux amongst young adults in three European countries

Abstract: The prevalence of snoring was about the same in all four areas, whilst there was a geographical variation in daytime sleepiness and tiredness. As complaints of DS and DT and disrupted breathing were more common in subjects who reported symptoms of gastro-oesophageal reflux, we suggest that polysomnographic studies comparing sleep patterns in adult patients with and without reflux should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
1
5

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 22 publications
6
44
1
5
Order By: Relevance
“…An association between HS and gastro-oesophageal reflux has been reported for adults [36]. For children, an association with posseting is a new finding.…”
Section: Association With Clinical Featuresmentioning
confidence: 87%
“…An association between HS and gastro-oesophageal reflux has been reported for adults [36]. For children, an association with posseting is a new finding.…”
Section: Association With Clinical Featuresmentioning
confidence: 87%
“…Snoring was positively correlated with age, male gender and body mass index in all areas. Remarkable associations were also found between symptoms of gastrooesophageal reflux and daytime sleepiness (OR 2.6 (1.5-4.4)), daytime tiredness (OR 4.5 (2.7-7.6)) and disrupted breathing (OR 3.8 (1.4-10)) [2]. Habitual (>3 episodes·week -1 ) difficulties inducing sleep were reported by 6-9%, and early morning awakenings by 5-6% of the subjects in all centres [3].…”
mentioning
confidence: 84%
“…Our overall impression is that central apnoea is far more common than generally accepted until now, especially when mixed apnoeas are also taken into account. However, it remains unclear to what extent the central apnoea syndrome contributes to the reported symptoms of daytime sleepiness [2,3].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In a recent European study performed in four centres, 5% of the males and 2-3% of the females reported snoring occurring every night. Daytime sleepiness, every day, was reported by about 5% [1]. These data are impressive taken into account the likelihood of underreporting in some specific populations [2].…”
Section: S Sl Le Ee Ep P a An Nd D B Br Re Ea At Th Hi In Ng G: : A Amentioning
confidence: 83%
“…Two percent of females and 4% of males in the middle-age group meet the minimal criteria for the sleep apnoea syndrome (AHI >5 and daytime hypersomnolence) [3]. These sleep-related breathing disorders are not only more frequent than initially thought, they are also responsible for excess mortality [4] and morbidity [1,5]. Therefore, we should probably enhance our efforts to improve the treatment and outcome of this disease.…”
Section: S Sl Le Ee Ep P a An Nd D B Br Re Ea At Th Hi In Ng G: : A Amentioning
confidence: 99%